How Aconiti Radix Cocta can Treat Gouty Arthritis Based on Systematic Pharmacology and UPLC-QTOF-MS/MS - Ye, Xietao; Wu, Jianxiong; Zhang, Dayong; Lan, Zelun; Yang, Songhong; Zhu, Jing; Yang, Ming; Gong, Qianfeng; Zhong, Lingyun (Frontiers in Pharmacology, 2021)
Gouty arthritis (GA) is a common metabolic disease caused by a long-term disorder of purine metabolism and increased serum levels of uric acid. The processed product of dried root of Aconitum carmichaeli Debeaux (Aconiti Radix cocta (ARC)) is used often in traditional Chinese medicine (TCM) to treat GA, but its specific active components and mechanism of action are not clear.First, we used ultra-performance liquid chromatography-quadrupole/time-of-flight tandem mass spectrometry to identify the chemical spectrum of ARC. Based on this result, we explored the active components of ARC in GA treatment and their potential targets and pathways. Simultaneously, we used computer simulations, in vitro cell experiments and animal experiments to verify the prediction results of systems pharmacology. In vitro, we used aurantiamide acetate (AA) to treat monosodium urate (MSU)-stimulated THP-1 cells and demonstrated the reliability of the prediction by western blotting and real-time reverse transcription-quantitative polymerase chain reaction (RT-qPCR). ELISAs kit were used to measure changes in levels of proinflammatory factors in rats with GA induced by MSU to demonstrate the efficacy of ARC in GA treatment.Forty-three chemical constituents in ARC were identified. ARC could regulate 65 targets through 29 active components, and then treat GA, which involved 1427 Gene Ontology (GO) terms and 146 signaling pathways. Signaling pathways such as proteoglycans in cancer, C-type lectin receptor signaling pathway, and TNF signaling pathway may have an important role in GA treatment with ARC. In silico results showed that the active components songoramine and ignavine had high binding to mitogen-activated protein kinase p38 alpha (MAPK14) and matrix metallopeptidase (MMP)9, indicating that ARC treatment of GA was through multiple components and multiple targets. In vitro experiments showed that AA in ARC could effectively reduce expression of MAPK14, MMP9, and cyclooxygenase 2 (PTGS2) in THP-1 cells stimulated by MSU, whereas it could significantly inhibit the mRNA expression of caspase-1, spleen tyrosine kinase(SYK), and PTGS2. Animal experiments showed that a ARC aqueous extract could significantly reduce expression of tumor necrosis factor-α, interleukin-1β, and intereleukin-18 in the serum of GA rats stimulated by MSU.